The effect of social media exposure towards fake news sharing behaviour in Abu Dhabi, UAE - Naseeb Balmuralmansoori, Ahmed Hamad (2022)
The growth in social media adoption has come with its benefits and threats. Mainly, the disinformation on social media platforms has emerged as a threat to public life and national stability. The UAE is not an exception in this case. The study aims to investigate the salience of the dangers posed by social media platforms to the national security of the Abu Dhabi Emirate. The national security threat is premised on the fake news sharing behaviour of social media users. To arrive at the main framework of reference, the study builds on the theory of planned behaviour and the theory of reasoned action. The quantitative research methodology using Partial Least Squares – Structural Equation Modelling (PLS-SEM) was employed. The research collected valid responses from 371 Facebook social media users within the two main Abu Dhabi Emirate cities of the Abu Dhabi Capital City and Al Ain City which was used for the analysis. The study found that the background factors of individual, social and knowledge experiences define social media platform exposure of social media users in Abu Dhabi. Exposure to social media has a significant effect on social media users' attitudes and perceived norms, but not perceived behavioural control. Nonetheless, attitudes and norms have no significant effect on behavioural intention to spread fake news. Only perceived behavioural control has an impact on fake news behavioural intention and actual fake news behaviour. The model fit was satisfactory with GoF index of 0.4951, and the SRMR, d_ULS, d-G, Chi-Square, NFI fit indices were all within the acceptable range. Thus, the data fit the theory adequately. The study contributes to the existing body of knowledge by establishing that fake news behavioural intention has a significant influence on social media users' actual fake news behaviour. The study also makes a novel contribution to knowledge by establishing the moderating effect of fake news sources on the relationship between behavioural antecedents and the fake news behavioural intention. It also shows that social media users' actual fake news behaviour varies depending on the perceived control the social media users have on fake news. The research recommended that the UAE Government research model shape public behaviour concerning social media exposure to minimise social behaviour threat.